2002
DOI: 10.1021/jp0259521
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Solid-State NMR Studies of Imidazole-Based Proton Conductors:  Structure Motifs and Chemical Exchange from 1H NMR

Abstract: High-resolution solid-state 1H NMR under fast magic angle spinning is used for the first time to study proton conductivity. The materials of interest, ethylene oxide tethered imidazole heterocycles (Imi-nEO), are characterized by variable temperature experiments, as well as 2D homonuclear double quantum (DQ) NMR and 2D exchange spectroscopy. Quantum chemical calculations provide a full assignment and understanding of the 1H chemical shifts, based on a single-crystal structure obtained for Imi-2EO. Three types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
225
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(242 citation statements)
references
References 23 publications
16
225
1
Order By: Relevance
“…A concentrated effort at fitting these line shapes, however, indicates the presence of two separate domains, in agreement with the findings of Goward and Spiess. 88,89 This is most easily illustrated by considering the simulations in Figure 9, which show how the 14 N powder pattern changes over a range of both jump rates and echo delays under the PH model. Two regimes can be distinguished.…”
Section: Urea-dmentioning
confidence: 99%
“…A concentrated effort at fitting these line shapes, however, indicates the presence of two separate domains, in agreement with the findings of Goward and Spiess. 88,89 This is most easily illustrated by considering the simulations in Figure 9, which show how the 14 N powder pattern changes over a range of both jump rates and echo delays under the PH model. Two regimes can be distinguished.…”
Section: Urea-dmentioning
confidence: 99%
“…The elucidation of the packing environment is often best investigated by looking at the proximities of the protons to each other using DQ filtered experiments. 6,7 Protons that are mobile on the timescale of the experiment are motionally averaged and filtered from the spectra. In the 1D DQF 30 kHz MAS NMR spectrum of fully dried choline DHP acquired using the Back-to-Back (BaBa) pulse sequence 6,18 at ambient temperature themselves (self-correlations E-E and F-F in Figure 6) and with each other (cross peaks E-F).…”
Section: H Nmr: Structure and Influence Of Drying Conditionsmentioning
confidence: 99%
“…Proton double-quantum filtered ( 1 H DQF) experiments have been used in the study of a large number of systems for determination of the packing arrangement of the hydrogen-bonding motifs. [6][7][8][9][10][11] These experiments access the information inherent to through-space dipolar coupling and the relative strength of the measured dipolar coupling can be used as a probe of molecular mobility.…”
Section: Introductionmentioning
confidence: 99%
“…High resolution NMR spectroscopy [5] has shown that, even below the melting point, the proton doped samples contain locally disordered domains with reduced dipolar interactions. These domains are believed to be associated with the local rearrangement of the hydrogen bonds (HBs), which, in turn, is related to the molecular motion and the proton diffusion.…”
mentioning
confidence: 99%
“…These domains are believed to be associated with the local rearrangement of the hydrogen bonds (HBs), which, in turn, is related to the molecular motion and the proton diffusion. The fast time scale of the rearrangement of the hydrogen bonds' patterns has prevented the determination of the microscopic diffusion mechanism [5]. However, an understanding of the diffusion mechanism is essential not only because of the relevance of proton conduction in very many areas of science, but also for a rational design of proton conductors with improved properties.…”
mentioning
confidence: 99%